External stability, real exchange rate adjustment and the exchange rate regime in emerging-market economies - Olivier Gervais; Lawrence Schembri; Lena Suchanek (Bank of Canada, 2011)
In emerging-market economies, real exchange rate adjustment is critical for maintaining a sustainable current account position and thereby for helping to reduce macroeconomic and financial instability. The authors examine empirically two related hypotheses: (i) that real exchange rate flexibility and adjustment promotes external stability, and (ii) that a flexible nominal exchange rate facilitates real exchange rate adjustment. Based on an event-study analysis for a large set of emerging-market economies over the period 1975-2008, the authors find that real exchange rate adjustment has contributed significantly to reducing current account imbalances. The adjustment of current account deficits in countries with a fixed exchange rate regime does not typically occur through the classical adjustment mechanism, but as a consequence of exchange rate crises, where the nominal exchange rate collapses and there are substantial costs in terms of forgone output. Vector-error-correction results support the findings of the event study; namely, in the long run the real exchange rate movements facilitate current account adjustment.
Keywords: F31; F32; F41; 330; Exchange rate regimes; International topics; Development economics; Gleichgewichtiges Wachstum; Zahlungsbilanzgleichgewicht; Wechselkurspolitik; Kaufkraftparität; Aufstrebende Märkte